IMPROVING THE ACCOUNTING AND AUDITING OF PRODUCTION COSTS IN INDUSTRIAL ENTERPRISES (International Congress on Economics, Management and Business Studies, 2026)
In the context of the globalization of the world economy and intensifying competition, the principal task facing industrial enterprises is to optimize product cost and increase production efficiency. It has been scientifically proven that contemporary systems for managing production costs (Lean Production, Kaizen, Activity-Based Costing) make it possible to reduce product cost by 15-20%. The Concept for the Socio-Economic Development of the Republic of Uzbekistan until 2030 establishes as a priority task the increase of industrial output by 1.4 times and a doubling - at minimum - of labor productivity in industrial sectors. The achievement of these indicators directly requires the introduction of new mechanisms for the classification, planning, and control of production costs at industrial enterprises.